Experiencing Transitional Democracy: The Role of the Anti-Marcos Opposition Groups - Lusterio, Ruth R. (Kasarinlan: Philippine Journal of Third World Studies; Vol 12 No 1 (1996): Democratic Transitions, 2008)
A Review of Mark Thompson's "The Anti-Marcos Struggle: Personalistic Rule and Democratic Transition in the Philippines"